The X-ray dust-scattered rings of the black hole low-mass binary V404 Cyg - Vasilopoulos, G.; Petropoulou, M. (OUP, 2016)
We report on the first detection of X-ray dust-scattered rings from the Galactic low-mass X-ray binary V404 Cyg. The observation of the system with Swift/XRT on 2015 June 30 revealed the presence of five concentric ring-like structures centred at the position of V404 Cyg. Follow-up Swift/XRT observations allowed a time-dependent study of the X-ray rings. Assuming that these are the result of small-angle, single X-ray scattering by dust grains along the line of sight, we find that their angular size scales as θ ∝ √{t} in agreement with theoretical predictions. The dust grains are concentrated in five dust layers located at about 2.12, 2.05, 1.63, 1.50 and 1.18 kpc from the observer. These coincide roughly with locations of enhanced extinction as determined by infrared photometry. Assuming that the grain size distribution is described by a generalized Mathis-Rumpl-Nordsieck model, we find that the power-law index of the most distant cloud is q ∼ 4.4, while q ∼ 3.5-3.7 in all other clouds. We constrain at a 3σ level the maximum grain size of the intermediate dust layers in the range 0.16-0.20 μm and set a lower limit of ∼ 0.2 μm in the other clouds. Hints of an exponential cutoff at the angular intensity profile of the outermost X-ray ring suggest that the smallest grains have sizes 0.01 ≤ αmin ≲ 0.03 μm. Based on the relative ratios of dust column densities we find the highest dust concentration at ∼1.6 kpc. Our results indicate a gradient in the dust properties within 1 kpc from V404 Cyg.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; dust; extinction; ISM: individual objects: V404 Cygni; X-rays: binaries; X-rays: ISM